Finite Element Simulation on Crack Analysis of a Thick-Tube - Ahmad Zaidi, A.M.; Md Asif, M.M.; Abdul Rahman, I.; Mohideen, S.Rasool; Ahmad Zaidi, A.F.; Ahmad Zaidi, N.H.; Yusof, M.S. (International Journal of Integrated Engineering, 2009)
Most engineering failure began with cracks. Crack may caused by material defect, discontinuities in geometry or damage in service. Thus, Fracture Mechanics is introduced as a method for predicting failure of a surface containing a crack. This project is focusing on pre-existing crack with assumption that no microscopic defects are presents. Linear Elastic Fracture Mechanics (LEFM) is used to evaluate the Stress Intensity Factor (SIF) of the specimen. Further analysis is done by incorporating Elastic Plastic Fracture Mechanics (EPFM) to understand the crack growth over period of time. In this study, the important parameters in fracture mechanics such as Stress Intensity Factor (SIF), Crack Mouth Opening Displacement (CMOD), J Integral and stable crack growth are been investigated. A complex loading simulation of NKS-3 specimen is done using finite element modeling. The NKS-3 is a thick-tube used in Pressurized Water Reactor (PWR) which has a circumferential flaw on its inner surface. The cylinder is loaded with axial tensile load and internal pressure combined with thermal shock. A 2-Dimensional Axysimmetric-4 nodes element with focused mesh at the crack tip is employed in the simulation. Several analyses have been done using hardening data at different temperature. A comparison of solution is made for simulation with and without thermal load history. Further analysis showed that the stable crack growth is estimated to be around 3.0mm.